AYAT-AYAT DOA DALAM AL QUR'AN PRESPEKTIF MAKNA DASAR DAN RELASIONAL - Rosyidi, Abdul Wahab (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2010)
One of approaches in comprehending al-Qur’an is semantic or meaning approach. There are three ways to goin the meaning; first is through microstructure, that is to get the meaning of text through structural analysis of sentence and phrase. Second, stylistic, that is the special stylistic of al-Qur’an to be the tool to find the meaning of the text. Third, semantic, that is the choice of word or vocabulary used in al-Qur’an has basic meaning and relational meaning. This paper is intended to observe the words that contain doa explicitly, that is the verse of doa with the key word “fi’il madhi, and amar”. The research belongs to library research of qualitative approach. After analyzing the key word, the conclusions are: 1) the basic meaning of the key word in the verse of doa in al-Qur’an has lexical meaning, while the relational meaning is the meaning produced by the textual and contextual, in this case the relational meaning of the verse of doa constitutes, of synonym, antonym, and ambiguity. 2) In the verse of doa in al-Qur’an, the relational meaning is not always attached to the key words; although it is related to the other words, it sometimes still has lexical meaning.